Mass Drug Administration With Artemisinin-Piperaquine for the Elimination of Residual Foci of Malaria in São Tomé Island - Li, Mingqiang; Tuo, Fei; Tan, Ruixiang; Zhang, Hongying; Zheng, Shaoqin; Wang, Qi; Xu, Qin; Yu, Xinbing; Lu, Fangli; Wu, Zhibing; Huang, Jun; Rampao, Herodes Sacramento; et al. (Frontiers in Medicine, 2021)
Background: Mass drug administration with artemisinin-piperaquine (AP-MDA) is being considered for elimination of residual foci of malaria in Democratic Republic of São Tomé and Principe. Methods: Three monthly rounds of AP-MDA were implemented from July to October 2019. Four zones were selected. A and B were selected as a study site and a control site, respectively. C and D were located within 1.5 and 1.5 km away from the study site, respectively. Parasite prevalence, malaria incidence, and the proportion of the Plasmodium falciparum malaria cases were evaluated. Results: After 3 monthly rounds of AP-MDA, the parasite prevalence and the gametocyte carriage rate of P. falciparum in zone A decreased from 28.29(‰) to 0 and 4.99(‰) to 0, respectively. Compared to zone B, the relative risk for the population with Plasmodium falciparum malaria in zone A was lower (RR = 0.458, 95% CI: 0.146–1.437). Malaria incidence fell from 290.49(‰) (the same period of the previous year) to 15.27(‰) (from the 29th week in 2019 to the 14th week in 2020), a decrease of 94.74% in zone A, and from 31.74 to 5.46(‰), a decline of 82.80% in zone B. Compared to the data of the same period the previous year, the cumulative number of P. falciparum malaria cases were lower, decreasing from 165 to 10 in zone A and from 17 to 4 in zone B. The proportion of the P. falciparum malaria cases on the total malaria cases of the country decreased of 90.16% in zone A and 71.34% in zone C. Conclusion: AP-MDA greatly curbed malaria transmission by reducing malaria incidence in the study site and simultaneously creating a knock-on effect of malaria control within 1.5 km of the study site and within the limited time interval of 38 weeks.